The Effect of Using Bromelain and Papain Enzymes on the Quality of Pure Fish Oil from Milkfish Silage (Chanos chanos) - Yosie Prayudha Arisky; Supriyanto Supriyanto; Mohammad Fakhry (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight ResearchMilkfish silage oil fatty acid profileThe quality of pure fish oil from milkfish silage (Chanos chanos)The effect of using bromelain and papain enzymesAbstractMilkfish has a high nutritional content, especially fat content. The processing of milkfish oil into pure oil has not been done much. Proper processing is needed so that the fatty acids contained in fish can be utilized optimally for pharmaceutical and medical needs. Enzyme extraction is known to extract fish oil with better quality than the heating method. The aim of this research was to study the effect of the enzymes bromelain and papain on the quality of pure fish oil from milkfish silage by treating different body parts used. The experiment was carried out with Factorial Complete Randomized Design with three replications involving two factors. The first factor was the type of enzyme using two types of enzymes, namely bromelain and papain with a concentration of 15%, the second factor used was the difference in body parts that was whole fish, flesh, and waste (head, viscera, and bones). The results showed that the type of enzyme had no significant effect on the quality of fish oil, but the different treatments of fish body parts had a significant effect on the quality of the fish oil produced. The best treatment was adapted from fish oil treated using the bromelain enzyme with the flesh. This treatment resulted in yield of 1.25%, density 0.903 g/mL, FFA content of 0.56%, and peroxide value of 7.64 meq/kg.